Pure Laparoscopic Living Donor Hepatectomy With/Without Fluorescence-Assisted Technology and Conventional Open Procedure: A Retrospective Study in Mainland China - He, Kang; Pan, Yixiao; Wang, Hai; Zhu, Jianjun; Qiu, Bijun; Luo, Yi; Xia, Qiang (Frontiers in Surgery, 2021)
Background: The application of laparoscopy in donor liver acquisition for living donor liver transplantation (LDLT) has become increasingly popular in the past decade. Indole cyanide green (ICG) fluorescence technique is a new adjuvant method in surgery. The purpose was to compare the safety and efficacy of laparoscopic and open surgery in living donor left lateral hepatectomy, and to evaluate the application of ICG in laparoscopy. Methods: Donors received LDLT for left lateral lobe resection from November 2016 to November 2020 were selected and divided into pure laparoscopy donor hepatectomy (PLDH) group, fluorescence-assisted pure laparoscopy donor hepatectomy (FAPLDH) group and open donor hepatectomy (ODH) group. We compared perioperative data and prognosis of donors and recipients. Quality of life were evaluated by SF-36 questionnaires. Results: The operation time of PLDH group (169.29 ± 26.68 min) was longer than FAPLDH group (154.34 ± 18.40 min) and ODH group (146.08 ± 25.39 min, p = 0.001). The blood loss was minimum in FAPLDH group (39.48 ± 10.46 mL), compared with PLDH group (52.44 ± 18.44 mL) and ODH group (108.80 ± 36.82 mL, p=0.001). The post-operative hospital stay was longer in PLDH group (5.30 ± 0.98 days) than FAPLDH group (4.81 ± 1.03 days) and ODH group (4.64 ± 1.20 days; p = 0.001). Quality of life of donors undergoing laparoscopic surgery was better. Conclusion: Laparoscopic approaches for LDLT contribute to less blood loss, better cosmetic satisfaction. The fluorescence technique can further reduce bleeding and shorten operation time. In terms of quality of life, laparoscopic surgery is better than open surgery. Laparoscopy procedure for living-donor procurement with/without fluorescence-assist can be performed as safely as open surgery.